2017
DOI: 10.2528/pierc17083001
|View full text |Cite
|
Sign up to set email alerts
|

A Miniaturized Self-Matched Negative Group Delay Microwave Circuit

Abstract: Abstract-A miniaturized self-matched negative group delay (NGD) microwave circuit without the need for external matching networks is proposed. The NGD circuit is based on a modified parallel-type RLC resonator, in which lumped elements (capacitors and inductors) are implemented by microstrip gaps and high-impedance and short-circuited microstrip lines. To verify the design concept, an NGD circuit with the size of 0.21λ g × 0.29λ g is designed and fabricated. From the measurement results, the NGD time of −5.9 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Shao et al [46] performed tensile tests on the macroscopic bamboo blocks (4 years old) and the mesoscopic bamboo fiber and showed that the tensile strength of bamboo fiber obtained from the tests on bamboo blocks was higher than that on separated fiber bundles. Habibi and Lu [47] studied crack growth mode in the hierarchical cellular structure of the 5 years old mature Moso bamboo and revealed that fibers' pull out was one of the prominent feature in tensile fracture surface.…”
Section: Introductionmentioning
confidence: 99%
“…Shao et al [46] performed tensile tests on the macroscopic bamboo blocks (4 years old) and the mesoscopic bamboo fiber and showed that the tensile strength of bamboo fiber obtained from the tests on bamboo blocks was higher than that on separated fiber bundles. Habibi and Lu [47] studied crack growth mode in the hierarchical cellular structure of the 5 years old mature Moso bamboo and revealed that fibers' pull out was one of the prominent feature in tensile fracture surface.…”
Section: Introductionmentioning
confidence: 99%